Three-dimensional ultrasound power Doppler assessment of the cervix: comparison between nulliparas and multiparas - (:unkn) unknown (WALTER DE GRUYTER & CO, 2007)
Aim: To assess the sonographic cervical characteristics between nulliparous and multiparous women. Subject and methods: Transvaginal three-dimensional ultrasound and power Doppler using the virtual organ computer-aided analysis (VOCAL) program were performed on 71 nulliparas and 59 multiparas at a mean gestational age of 25.3 +/- 7.9 weeks. We compared the cervical volume and power Doppler vascularization index (VI), flow index (FI), and vascularization-flow index (VFI) between nulliparas and multiparas. Results: The mean cervical volume and mean VI, VFI, FI measurements were not significantly different between multiparas and nulliparas. Conclusion: Our observations suggest that the morphological changes in the cervix of parous women are merely configurational without a change in cervical mass and vascularization. These configurational changes might result from the inevitable cervical streching during labor and represent a healing process that does not involve a subsequent change in mass or vascularity.
Keywords: cervical volume; parity; power Doppler; pregnancy; three-dimensional ultrasound; PREGNANCY; SONOGRAPHY; GESTATION; WOMEN